Evidence of a role for B cell–activating factor of the TNF family in the pathogenesis of chronic rhinosinusitis with nasal polyps - Kato, Atsushi (2008)
BACKGROUND: The polypoid form of chronic rhinosinusitis (chronic rhinosinusitis with nasal polyps [CRSwNP]) is a highly prevalent disease that often requires surgical intervention for treatment. Nasal polyps contain large quantities of B lymphocytes and immunoglobulin as well as eosinophils. OBJECTIVES: The objective of this study was to investigate the expression of B cell–activating factor of the TNF family (BAFF), an important regulator of class-switch recombination and immunoglobulin production, in patients with chronic rhinosinusitis (CRS). METHODS: We collected nasal tissue and nasal lavage fluid from patients with CRS and control subjects. We assayed mRNA for BAFF and B-lymphocyte markers, CD20 and transmembrane activator and calcium-modulator and cyclophilin ligand interactor, by using real-time PCR, and assayed BAFF protein by using ELISA and immunohistochemistry. RESULTS: BAFF mRNA was significantly increased in nasal polyps from patients with CRSwNP (P < .001) compared with inferior turbinate tissue from patients with CRS or healthy subjects. BAFF protein was also elevated in polypoid tissue and nasal lavage from patients with CRSwNP. Immunohistochemistry showed considerable BAFF staining in mucosal epithelial cells in nasal polyps along with unidentified cells in the lamina propria. Expression of mRNA for BAFF in sinonasal tissue was significantly correlated with CD20 and transmembrane activator and CAML interactor in sinus tissue. IgA, an immunoglobulin isotype known to activate eosinophils, was also significantly elevated in the polypoid tissue. CONCLUSION: Overproduction of BAFF in nasal polyps may contribute to the pathogenesis of CRSwNP via the local induction of IgA and activation of eosinophils.